Pengaruh IMT (Indeks Masa Tubuh) Dan Aktivitas Fisik Terhadap Dismenore Pada Remaja Putri Di SMK Cendikia Madinah Dampit - Melda Yulia Putri; Tut Rayani Aksohini Wijayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Puberty is an important stage where the reproductive organs mature and the first menstruation occurs. Many girls experience pain during menstruation, known as dysmenorrhea, and in Indonesia, around 55% of girls experience it, with 15% feeling that their daily activities are disrupted. This study analyzed the effect of body mass index (BMI) and physical activity on dysmenorrhea in adolescent girls. The method used was descriptive and cross-sectional, conducted between June and July 2025, with data collected through questionnaires. The results showed that BMI and physical activity affected dysmenorrhea.